Guerra, impuestos y reformas financieras: las colonias españolas e inglesas del siglo XVIII - Brown, Kendall W. (2015)
After the Seven Years War ended in 1763, Spain undertook fiscal reforms not only to pay for the costs of the conflict but also to improve imperial defenses. New and increased taxes led to colonial resistance. Meanwhile, the British Parliament imposed new taxes on its American subjects. In the British case, fiscal demands drove the Thirteen Colonies out of the empire, whereas in the Spanish colonies, the resistance provoked by the new fiscal policies did not lead to independence. This paper will examine some of the reasons for the different outcomes in British and Spanish America.